OPTIMIZATION PROCESS OF TEMPERATURE AND SODIUM BISULPHITE (NAHSO3) CONCENTRATION ON THE PRODUCTION OF SODIUM LIGNOSUPHONATE BASED ON PALM EMPTY FRUIT BUNCH(EFB) - Ani Suryani, Djumali Mangunwidjaja, Erliza Hambali dan Kosi Anwar (Jurnal Teknologi Industri Pertanian, 2008)
ABSTRACTSurfactant development is not just to find new variant of surfactant that can  be used in  industries, but it’s for finding new raw material that potential for surfactant production. One of the potentially raw materials for surfactant production is palm empty fruit bunch (EFB). That material is potential for surfactant lignosuphonate production because it contain lignin component, that is  22.21% and  it is not used optimally yet. The purposes of this research is to optimize  the using of palm empty fruit bunch (EFB) with carry out investigation in optimization of temperature and concentration of sulphonation agent  to the yield and solubility of the sodium lignosulphonate. The experimental  design that was used is two level factorial and optimization methode that was used is response surface methode. Level of temperature in this experiment is 80-100oC and sodium bisulphite concentration that was used is 40-60% (b/b). The experiment result showed that the reaction temperature and sodium bisulphite concentration had positive influence to the sodium lignosulphonate yield with significant value 98% and 99%.  Beside that, reaction temperature and sodium bisulphite concentration had also a positive influence  to the sodium lignosulphonate solubility with significant value is 58% and 65%. The result of canonic analysis to the response surface of sodium lignosulphonate yield from sodium bisulphite concentration factor (X1) and temperature (X2) showed that the model shape was saddle point. The analysis of  the result of optimum condition showed that the highest yield  is 80.19% (b/b) at sodium bisulfate concentration of 53.25% (b/b) and temperature of 103.76oC. Validation result in this condition showed that sodium lignosulphonate yield was 61.48%. The result of canonic analysis to sodium lignosulphonate solubility from sodium bisulphite concentration factor (X1) and temperature (X2) showed that the model optimum from statistical analysis of sodium lignosulphonate solubility was 97.2% at sodium bisulphite concentration of 53.49% (b/b) and temperature of 94.95oC. Validation result in this condition showed that sodium lignosuphonate solubility was 96%.Keywords : palm empty fruit bunch; organosolv lignin; sodium lignosulphonate; response  surface method